Analysis, design and simulation of metal PBG waveguide - Thottappan M.; Jain P.K. (My University, 2025)
This article deals with analysis, design, modeling and simulation of a metal photonic band gap (MPBG) waveguide for TE mode of operation. The finite difference time domain (FDTD) technique has been used to analyze and obtain the global band gap regions of the MPBG structures having 2-D triangular array. A mode map diagram has been developed for the MPBG waveguide in order to study the propagation characteristics of the guide. The designed waveguide structure has been cold characterized using a 3-D electromagnetic code for the desired TE01 mode. This study shows that nearby competing modes, like, TE21 and TE31 have been suppressed and ensures that the MPBG is been preponderant for waveguide applications and also it addresses the mode competition, miniaturization and the power handling issues which generally appears at the short wavelengths. The transmission loss over the guide has been estimated through its scattering coefficients as 1.01 dB /cm at the operating frequency. © 2013 IAMOT.